Hypoventilation disproportionate to OSAS severity in children with Prader-Willi syndrome. Issue 2 (22nd February 2019) - Abel, Francois; Tan, Hui-Leng; Negro, Valentina; Bridges, Nicola; Carlisle, Thomas; Chan, Elaine; Laverty, Aidan; Miligkos, Michael; Samuels, Martin; Kaditis, Athanasios G
Abstract : Objective: To test the hypothesis that children with Prader-Willi syndrome (PWS) and obstructive sleep apnoea syndrome (OSAS) have hypercapnia for higher proportion of total sleep time (TST) than non-syndromic children with similar obstructive apnoea–hypopnoea index (OAHI). Design: Cross-sectional study. Setting: Two tertiary care hospitals. Patients: Patients with PWS and non-syndromic children with snoring who underwent polygraphy and were of similar age, body mass index (BMI) z-score and OAHI. Main outcome measure: The two groups were compared regarding %TST with transcutaneous CO2 (PtcCO2 ) >50 mm Hg. The interaction between PWS diagnosis and OSAS severity (OAHI <1 episode/h vs 1–5 episodes/h vs >5 episodes/h) regarding %TST with PtcCO2 >50 mm Hg was tested using multiple linear regression. Results: 48 children with PWS and 92 controls were included (median age 2.3 (range 0.2–14.1) years vs 2.2 (0.3–15.1) years; BMI z-score 0.7±1.9 vs 0.8±1.7; median OAHI 0.5 (0–29.5) episodes/h vs 0.5 (0–33.9) episodes/h; p>0.05). The two groups did not differ in %TST with PtcCO2 >50 mm Hg (median 0% (0–100%) vs 0% (0–81.3%), respectively; p>0.05). However, the interaction between PWS and OSAS severity with respect to duration of hypoventilation was significant (p<0.01); the estimated mean differences of %TST with PtcCO2 >50 mm Hg between children with PWS and controls for OAHI <1 episode/h, 1–5 episodes/h and >5 episodes/h were +0.2%, +1% and +33%, respectively. Conclusion: Increasing severity of upper airway obstruction during sleep in children with PWS is accompanied by disproportionately longer periods of hypoventilation when compared with non-syndromic children with similar frequency of obstructive events.